Intimate partner violence among Arab women before and during the COVID-19 lockdown - Nessrin A. El-Nimr; Heba M. Mamdouh; Amal Ramadan; Haider M. El Saeh; Zeinab N. Shata (SpringerOpen, 2021)
Abstract Introduction Intimate partner violence (IPV) remains a serious human rights violation and an important health concern during the ongoing COVID-19 pandemic. The study aims to estimate the proportion of IPV among adult Arab women before and during the COVID-19 lockdown and to identify its possible predictors during the lockdown. Methods A cross-sectional study was conducted between April and June 2020 using an online questionnaire. The sample included 490 adult Arab women aged 18 years and above, who live with their husbands. Data was collected using a Google forms designed questionnaire that included the socio-demographic characteristics, nature of lockdown, and exposure to different types of IPV before and during COVID-19 lockdown and the frequency of their occurrence. McNemar's test was used to determine differences in the exposure to IPV before and during the lockdown, while logistic regression analysis was performed to identify the predictors of exposure to IPV during the lockdown. Results Half of women reported that they were ever exposed to IPV with psychological violence ranking 1st. Exposure to any type of IPV and exposure to psychological, physical, and sexual violence have significantly increased during the lockdown compared to before the lockdown. The frequency of exposure to the different types of IPV ranged from 1-3 times per month to almost every day, but the most commonly reported was 1-3 times per month. Predictors of exposure to IPV during the COVID-19 lockdown included country of residence, family income, and whether the husband lost his job during lockdown. Conclusions IPV has increased during the COVID-19 pandemic lockdown in the Arab countries, and it was associated with the socioeconomic consequences of the pandemic on families. Actions towards raising awareness about the problem among professionals and the community, early detection, and provision of appropriate services are mandatory.